Is The SARS-CoV2 Evolved in Human Being: A prospective Genetic Analysis - Dimonte, Salvatore; Jamal Jalal, Paywast; Abdulrahman Ahmad, Hiwa; Bakr Karim, Safa; Ahmed Hama Soor, Taib; Ibrahim Ali, Salar; Babakir-Mina, Muhammed; Greco, Francesco (Kurdistan Journal of Applied Research, 2020)
COVID-19 is the deadly respiratory disease of the century caused by new type unknown origin Coronavirus. The recent effort of the word researchers is toward finding the origin of the virus. The current study investigated the extent of molecular similarity and divergence between SARS-CoV2 and other related Coronavirus. An attempt has been made to investigate the epidemiological study of this new contagious virus using molecular biology techniques. The phylogenetic trees for all human coronaviruses with the novel Coronavirus have been built using a several complete amino acid sequences of the four known structural proteins, S (spike), E (envelope), M (membrane), and N (nucleocapsid). The result of the study revealed that the SARS-CoV2 is related to human SARS-CoV isolated from different countries very cloely, especially those strains recovered from China in recent times, 2020. The evolutionary changes observed in the inserted 23 amino acids in the RNA binding domain (RBD) of the coronvirus spike glycoprotein which cannot be detected in any other human coronavirus. Moreover, the 2019-nCoV is not closely related to other alpha, beta and gamma human Coronavirus, including MERS-CoV. The current study concluded that 2019-nCoV is more likely believed to originated from SARS-CoV. The probability is more vital to be originated from the strain isolated in China in 2020, which is coincident with the spraed of COVID-19 in the same country. The phyloepidemiologic analyses suggested that the coronaviruses are circulating in human hosts evolving gradually by times in response to the different environment stimuli facing the virus inside the host in different geographical areas. Furthermore, the analysis showed the flow of transmission, and evolutionary changes of SARS-CoV2 which may be directed from the transmission of SARS-CoV from human to Bat and Pangolin then jumped to human again in the crowded market Wuhan city in China.